Tourism destination development by hotel industry investment - Albert Tóth, Attila (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2016)
Developments are needed in each phase of the life cycle of the areas of tourism. Without them it would not be possible for any areas, even with tourist attractions, to become a really successful tourism destination. The development of basic infrastructure and tourism superstructure, including hotel investments, is of high importance, because the increase of the number of tourists, overnight stays and income can only be ensured by them. Even in the phase of stagnation, investment in hotels is essential in order to maintain and possibly improve the quality of services, rather than increasing capacity. Therefore, the main objective is to avoid decline. This paper introduces different features of investments in the hotel industry through the analysis of the life cycle model of tourism reception areas and hotel real estate development, using international and national examples.